PENGARUH LITERASI KEUANGAN, DIGITALISASI KEUANGAN, DAN MODAL USAHA TERHADAP KEBERLANJUTAN UMKM: STUDI KASUS UMKM KERAJINAN BAMBU DI DESA WISATA SENDARI, KECAMATAN TIRTOADI, KALURAHAN MLATI, KABUPATEN SLEMAN - Dwi Ayu Kurniawati, Fahmi; Sri Utami, Endang (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the influence of financial literacy, financial digitalization, and business capital on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Sendari Tourism Village, Tirtoadi Village, Mlati District, Sleman Regency. The background of the study stems from the problems of low understanding of MSMEs in financial management, limited access to capital, and low implementation of digitalization in financial activities that impact business sustainability. The research method used is quantitative with a multiple linear regression analysis approach using the SPSS version 21 program. The population of this study was all bamboo craft MSMEs in Sendari Tourism Village with a total of 45 respondents taken using a saturated sampling method. Data were collected through a questionnaire using a Likert scale. The results of the study indicate that financial literacy, financial digitalization, and business capital have a positive and significant effect on the sustainability of MSMEs. These findings confirm that increasing financial literacy capabilities, the use of digital technology in financial management, and the availability of adequate business capital are important factors in supporting the sustainability and development of MSMEs.